2017
DOI: 10.1080/13669877.2017.1351472
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction: psychosocial correlates, risky attitudes, and smartphone harm

Abstract: Smartphone use has brought convenience to users, although its excessive use and addiction might also have negative consequences. Using a representative sample of 526 smartphone users in Spain, the present study analyzes smartphone extensive use and addiction as well as its relationship to smartphone harm. Selfreported and scanned data were obtained from users and their smartphones. Multivariate linear regression analyses showed that higher levels of smartphone extensive use were found for female respondents, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 48 publications
2
27
0
3
Order By: Relevance
“…Dysfunctional attitude is a condition that may be experienced by individuals suffering from depression. The study by Herrero et al, which used 526 students, reported that smartphone users who received little social support experienced higher levels of smartphone addiction. In a study using 2017 academic year university students, reported that dysfunctional attitudes and negative automatic thoughts may cause an increase in depression levels.…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional attitude is a condition that may be experienced by individuals suffering from depression. The study by Herrero et al, which used 526 students, reported that smartphone users who received little social support experienced higher levels of smartphone addiction. In a study using 2017 academic year university students, reported that dysfunctional attitudes and negative automatic thoughts may cause an increase in depression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on smartphone addiction represent a continuation of the first studies on addiction to the Internet and to mobile phones and share some of their premises (Herrero et al, 2017a;Herrero, Urueña, Torres, & Hidalgo 2019). For example, these studies share the idea that communication technologies can lead to social isolation, which has negative consequences for well-being.…”
Section: Adicción a Los Teléfonos Inteligentes Y Apoyo Social: Un Estmentioning
confidence: 99%
“…They also share the idea that smartphone addiction have the same negative consequences stemming from behavioral addictions (such as gambling, for example), like poor psychological adjustment, problems at work, or an increase in conflicts with family and friends. The study of smartphone addiction has also brought some novelties like its effects on potential increases of security vulnerabilities and potential exposure to future cyber victimizations (for instance, phishing) (see Herrero et al, 2017a for an analysis).…”
Section: Adicción a Los Teléfonos Inteligentes Y Apoyo Social: Un Estmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, studies on excessive use predominantly relied on convenience samples, mostly university students, [9][10][11][12][13][14][15] and only very few researchers have investigated a representative or quota-based sample. 4,16 However, as smartphone use is not limited to young adults, including a broad age range of users is important. For example, in Germany, where the study has been conducted, 78% of citizens own a smartphone.…”
Section: Introductionmentioning
confidence: 99%